(untitled) (Research, Society and Development, 2021)
Patients with special needs tend to be defensive or exhibit extreme anxiety reactions during conventional dental attendance, requiring treatment in hospital facility, under general anesthesia. A patient diagnosed with autism was attended at the CAOE clinic (FOA/UNESP). In the clinical and radiographic evaluation, the need for dental procedures was detected, including endodontic treatment. Due to non-cooperation, the patient was referred to the hospital Santa Casa de Misericórdia. This report describes endodontics in a single session of three elements under general anesthesia. After sedation, coronary access of the 3 dental elements was performed, followed by rubber dam absolute isolation. The biomechanical prepare of root canals was performed using a mix technique: cervical/middle third preparation with Gates-Glidden drills and manual files for apical instrumentation, under irrigation of 2.5% sodium hypochlorite. The tooth length and working length were obtained with the aid of foraminal Root ZX II locator. After using 17% EDTA, new irrigation with sodium hypochlorite and drying root canals, the obturation was achieved. A calcium hydroxide-based sealer Sealapex was used with lateral condensation technique, followed by definitive restoration with composite resin. Endodontic treatment, even with the complexities of these conditions, is indicated to avoid extractions, since these patients present early tooth loss due to deficient oral hygiene by lack of motor skills. The survival rate of endodontically treated teeth under general anesthesia was favorable in the literature, as well as reports of improvement in life quality of patients with special needs.